Evaluation of the long-lasting insecticidal net Interceptor LN: laboratory and experimental hut studies against anopheline and culicine mosquitoes in northeastern Tanzania - Malima, Robert (BioMed Central, 2013)
BACKGROUND: Long lasting insecticidal nets (LN) are a primary method of malaria prevention. Before new types of LN are approved they need to meet quality and efficacy standards set by the WHO Pesticide Evaluation Scheme. The process of evaluation has three phases. In Phase I the candidate LN must meet threshold bioassay criteria after 20 standardized washes. In Phase II washed and unwashed LNs are evaluated in experimental huts against wild, free flying anopheline mosquitoes. In Phase III the LN are distributed to households in malaria endemic areas, sampled over three years of use and tested for continuing insecticidal efficacy. Interceptor® LN (BASF Corporation, Germany) is made of polyester netting coated with a wash resistant formulation of alpha-cypermethrin. METHODS: Interceptor LN was subjected to bioassay evaluation and then to experimental hut trial against pyrethroid-susceptible Anopheles gambiae and An. funestus and resistant Culex quinquefasciatus. Mosquito mortality, blood feeding inhibition and personal protection were compared between untreated nets, conventional alpha-cypermethrin treated nets (CTN) washed 20 times and LNs washed 0, 20 and 30 times. RESULTS: In Phase I Interceptor LN demonstrated superior wash resistance and efficacy to the CTN. In the Phase II hut trial the LN killed 92% of female An. gambiae when unwashed and 76% when washed 20 times; the CTN washed 20 times killed 44%. The LN out-performed the CTN in personal protection and blood-feeding inhibition. The trend for An. funestus was similar to An. gambiae for all outcomes. Few pyrethroid-resistant Cx. quinquefasciatus were killed and yet the level of personal protection (75-90%) against Culex was similar to that of susceptible An. gambiae (76-80%) even after 20 washes. This protection is relevant because Cx. quinquefasciatus is a vector of lymphatic filariasis in East Africa. After 20 washes and 60 nights’ use the LN retained 27% of its initial insecticide dose. CONCLUSIONS: Interceptor LN meets the approval criteria set by WHO and is recommended for use in disease control against East African vectors of malaria and filariasis. Some constraints associated with the phase II evaluation criteria, in particular the washing procedure, are critically reviewed.